Citizen participation in China's eco-city development. Will 'new-type urbanization' generate a breakthrough in realizing it?. (20th September 2017) - Li, Huifeng; de Jong, Martin
Abstract: China's recently adopted 'new-type urbanization' policy puts a heavier emphasis on the social and environmental aspects of urban development than previous plan documents. This includes the aspect of citizen participation and a stronger bottom up orientation in decision-making processes, the aspect this paper homes in on. We will examine the realities of citizen participation in eco-city development in China at the local level and do this in one of the most prosperous and administratively forward looking cities in China, Suzhou. The analytical framework with which this analysis is conducted is a combination of Arnstein's participation ladder and the three dimensions in Fung's cube. The two cases we have studied are an eco-city project in a village community and one in the old city, to ensure we cover two different modes of participation, one rural and one urban. Three dimensions (participant selection, mode of communication and conversion of discussion output into action) and two policy making phases (decision-making and implementation) are applied to allow for a systematic comparison of the two cases. We find that citizen participation in the rural community is far more collectivist and reactive, while that in the urban setting is more individualist and proactive. Furthermore, in both cases, citizen input in the decision-making phase is quite limited, while during implementation local government appreciates the support and practical input locals can supply. To further enhance citizen participation along the lines proposed in 'new-type urbanization', legislative reform and professionalization of officials in dealing with bottom-up input would be essential. Highlights: The extent of citizen participation differs markedly between the decision-making and implementation phases. A certain amount of distrust between officials and residents persists in the process of participation. Further reforms require changes in the legislation, the professionalization of government officials and civic awareness.